Revisiting higher education: Identifying the support needs of fractional academic staff teaching online - Kaur Saminder Singh, Gurdip; Kaur Sidhu, Gurnam; Ramasamy, Rajesvari; Madhawa Nair, Subadrah (Edelweiss Applied Science and Technology, 2024)
Fractional, or part-time teachers, commonly referred to as 'tutors,' have long been integral to higher education worldwide. Today as more and more universities are switching their educational modes to online and hybrid teaching and learning, a consequence of post Covid-19, the necessity to hire more online fractional academic staff has become even greater. However, for decades their role is often neglected, and they frequently lack the support required to fulfil their teaching responsibilities effectively. In the context of Malaysia, to date very limited empirical finding is available that investigates the support needs of fractional academic staff teaching online. The study reported in this paper is part of a larger study on higher education professional development among adjunct faculty. Understanding the needs of one of the largest faculties can offer valuable insights for enhancing the quality of online education. The main purpose of the study was to explore the support needs of fractional academic staff teaching online as perceived by the tutors themselves. The study adopted a mixed-method research design, utilizing questionnaire for quantitative approach followed by focus-group discussion as the qualitative approach. To understand if tutors were significantly more interested in one form of support to another, a Kruskal-Wallis ANOVA analysis was used. As for data obtained through focus-group discussion, thematic analysis was applied to identify most important and least important topics. The findings of the study revealed that fractional staff teaching online required four support needs, namely, professional support which included continuous online training programmes and seminars, structured operations and organizations that provide well-defined job descriptions related to their teaching roles, better recognition for their valuable contributions as well as better facilities by providing equitable workspace facilities. This study has crucial implications that suggest a need for a more inclusive and supportive approach to managing and developing fractional academic staff, particularly those involved in online education.